An Ability in Translating Recount Text by Using Translating Strategies - Mardin Silalahi; Rohdearni Wati Sipayung (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This research is focused on the ability of the students in translating a recount text by using translating strategies at the first grade students of SMA Swasta Yayasan Perguruan Keluarga (YPK) Pematangsiantar. This study tries to find out: 1) The translation strategy that are used by the students in the translating of a recount text; 2) The  translation  strategy  that  is  mostly  used  by  the  students  in  the translating of a recount text; 3) The  students’  perception  towards  the  translating  tasks  as  an  alternative task to enhance their reading habit and vocabulary. From the data analysis it can be concluded that: 1) In translating  the  recount text entitled Borobudur, especially  in dealing with  certain  words,  the  students  employ  ten  translation strategy.  These strategies are taken from the Newmarks’ translation strategy (1988:  81-93).  The strategies  which  are applied by the  students in  this  study  are  the transference  strategy,  the  naturalization  strategy,  the  cultural  equivalent strategy,  the  shift  or  transposition  strategy,  the  modulation  strategy,  the recognized  translation  strategy,  the  compensation  strategy,  the  expansion strategy, the couplets strategy, and the triplets strategy; 2) The  cultural  equivalent  strategy  is  the  one  which  is  mostly  used  by  the students  in  translating  the  text.  Based  on  Newmark  (1988:  82-83),  this  strategy  is  commonly found in translating popular fiction texts; 3) The  students’  perception towards  the translating  tasks  which are  given by their  teacher  is  that  the  translating  tasks  can  help  them  enhance  their reading  habit  and  increase  their  vocabulary.  The  reason  behind  this perception  is because  they  admit that they even do not  read  English  texts unless  their  teacher  has them  do  so.  In  this  case,  it  is  obviously seen  that the  students  agree  that  the  translating  task  is  an  alternative  task  to  make them  read  English  texts.  Although  in  the  reality  translating  task  is neglected  by  many  educators,  since  it  is  included  into  one  of  the characteristics of the Grammar Translation  method  which  is assumed only to  focus  on  knowing  grammar rules, remember  vocabularies, and produce a good translation of target language.